Enhanced hydrogen evolution reaction of WS2–CoS2 heterostructure by synergistic effect. (8th January 2019) - Jing, Yaqi; Mu, Xiaoyu; Xie, Chengwang; Liu, Haile; Yan, Ruijuan; Dai, Haitao; Liu, Changlong; Zhang, Xiao-Dong
Abstract: Transition metal dichalcogenides (TMDs) have attracted significant research interest due to its promising performance in hydrogen evolution reaction (HER). Synergistic effect between materials interface can improve the electrocatalytic properties. In this work, the WS2 –CoS2 heterostructure supported on carbon paper (CP) was elaborately fabricated by a three-step method. Owing to the synergistic effect, WS2 –CoS2 heterostructure exhibits an excellent electrocatalytic activity with a low overpotential of 245 mV at 100 mA/cm 2 and a small Tafel slope of 270 mV/dec toward HER. We demonstrate that the increased specific surface area and conductivity of the heterostructure play a key role in enhancing the overall catalytic efficiency. Moreover, the crystal lattice distortion in the heterostructure could induce charge redistribution and improve electron transfer efficiency, which may also benefit the whole HER activity. Graphical abstract: Image 1 Highlights: Non-noble metal catalyst with excellent activity toward HER. Facile synthesis method at common conditions. Synergistic effect in the heterostructure has been revealed by structural characterization.